TECHNOLOGY FOR THE PREPARATION OF DIDACTIC GAMES IN GENERAL AND MEDICAL RADIOBIOLOGY "TEACHING SCIENCE" IN HIGHER EDUCATION - E.X. Bozorov; F. N. Temirov; M.X. Jalilov; B. N. Burxonov; J. X. Xamroyev; M. N. Ahrorov; X. M. Jalilov (American Journals, 2023)
In the article, the selection of didactic games in teaching the subject "Itis mummified and medical radio and ology" is based on the prospects for the near future development of medical radio and ology, the further technical improvement of devices and their use as elements of two games the selection of tweaters, the promotion of comprehensive development of the experience of communication with peers and adults, and the interest in training.
Keywords: General and medical radiobiology, didactic games, gaming technology, training sessions, didactics, training activities, mentally activeyachts, knowledge and skills, skills and experience, games.